Efektifitas Manajemen Penghimpunan Zakat Pada Badan Amil Zakat Nasional (BAZNAS) Kota Ternate - Maskur Sapsuha; Basaria Nainggolan (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2021)
The Effectiveness of Zakat Collection Management at the National Amil Zakat Agency (BAZNAS) of Ternate City-This study aims to analyze the effectiveness of the management of zakat fund collection carried out by the amil zakat agency. The National Amil Zakat Agency (BAZNAS) is a state institution authorized to administer (collect) zakat, infaq, and shodaqoh. The BAZNAS Ternate collects zakat from Civil Servants in the Ternate City Government. However, the realization of the collection of zakat from civil servants has not been effective, as indicated by the low amount of zakat collected from civil servants. Qualitative field research method with primary data is interviews with BAZNAS Ternate commissioners and secondary data documents relevant to the management of zakat fund collection in BAZNAS Ternate city. The results of the study stated that the management of zakat collection was less effective because of the weakness of the prospective muzakki outreach strategy, inappropriate socialization methods, and lack of publicity.